1997
DOI: 10.3171/foc.1997.2.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Hemicraniectomy with dural augmentation in medically uncontrollable hemispheric infarction

Abstract: Surgical decompression to alleviate raised intracranial pressure has been reported repeatedly in the past decades in small series of patients. Only recently have there been indications from larger trials that surgical decompression may be beneficial in treating space-occupying hemispheric infarction. However, surgical requirements for the procedure to be effective have not yet been defined. Based on theoretical criteria, the authors operated on 43 patients with medically uncontrollable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 23 publications
2
30
1
6
Order By: Relevance
“…Recent studies have shown that early decompressive hemicraniectomy decreases mortality to 16-42 % [4, 6, 15, 16, 17, 26, 27, 31, 32, 33, 34, 38]. The aim of decompressive surgery is to give room for expansion of the swelling, restore cerebral perfusion and optimize retrograde perfusion through leptomeningeal collateral vessels [7,40]. Since young patients are especially affected by malignant middle cerebral infarctions, in addition to reducing the death rate, lowering morbidity and improving quality of life are essential goals of decompressive hemicraniectomy.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have shown that early decompressive hemicraniectomy decreases mortality to 16-42 % [4, 6, 15, 16, 17, 26, 27, 31, 32, 33, 34, 38]. The aim of decompressive surgery is to give room for expansion of the swelling, restore cerebral perfusion and optimize retrograde perfusion through leptomeningeal collateral vessels [7,40]. Since young patients are especially affected by malignant middle cerebral infarctions, in addition to reducing the death rate, lowering morbidity and improving quality of life are essential goals of decompressive hemicraniectomy.…”
Section: Introductionmentioning
confidence: 98%
“…The opening of the dura was performed in a stellate fashion, and the exposed brain was covered by the loosely replaced dura, then covered with Surgicel (Ethicon, Inc., NJ) in accordance with the rapid closure technique. [14][15][16] …”
Section: Decompressive Craniectomymentioning
confidence: 99%
“…This conclusion is validated by the fact that some studies suggest that doubling the diameter from 6 cm to 12 cm potentially increases the decompressive volume from 9 to 86 ml. 26,29 Ideally, hemicraniectomy should be performed in the frontotemporoparietal region and reach the floor of the middle cranial fossa. The midline should be spared to avoid injury to the superior sagittal sinus.…”
Section: Surgical Technique and Craniectomy Sizementioning
confidence: 99%